Analysis of Tospovirus resistance factors in Solanum (section Lycopersicon) accessions - Renata Maria de Oliveira; Marcos Gomes da Cunha; Maria Esther Noronha Fonseca; Leonardo Silva Boiteux; Érico de Campos Dianese (Pesquisa Agropecuária Tropical, 2015)
The intensive and uninterrupted tomato cultivation has favored the establishment of several diseases that affect fruit yield and quality. Genetic resistance is the best method to control the disease called 'vira-cabeça' (caused by distinct species of the genus Tospovirus), being Sw-5 the first resistance gene effectively identified to control it in tomato plants. This study aimed at identifying new potential sources of tospovirus resistance in wild Solanum(Lycopersicon) species, as well as performing phylogenetic analysis related to the evolutionary characteristics of the Sw -5b gene, in accessions of wild tomato species. These analyses showed that the different tomato species belong to distinct evolutionary groups. Most of the accessions with wide-spectrum resistance to Tospovirus species correspond to allelic variants closely related to the original Sw-5b gene copy. However, resistant accessions of S. chilense and S. habrochaites are located in distinct phylogenetic groups, meaning that they may represent promising sources of new genes/alleles, providing wide resistance to tospovirus.